Ubiquitin-specific peptidase 18 regulates the differentiation and function of Treg cells - Lu Yang; Yukai Jing; Danqing Kang; Panpan Jiang; Na Li; Xinrong Zhou; Yan Chen; Lisa S. Westerberg; Chaohong Liu (Genes and Diseases, 2021)
Ubiquitin-specific peptidase 18 (USP18) plays an important role in the development of CD11b+ dendritic cells (DCs) and Th17 cells, however, its role in the differentiation of other T cell subsets, especially in regulatory T (Treg) cells, is unknown. In our study, we used Usp18 KO mice to study the loss of USP18 on the impact of Treg cell differentiation and function. We found that USP18 deficiency upregulates the differentiation of Treg cells, which may lead to disrupted homeostasis of peripheral T cells, and downregulates INF-γ, IL-2, IL-17A producing CD4+ T cells and INF-γ producing CD8+ T cells. Mechanistically, we also found that the upregulation of Tregs is due to elevated expression of CD25 in Usp18 KO mice. Finally, we found that the suppressive function of Usp18 KO Tregs is downregulated. Altogether, our study was the first to identify the role of USP18 in Tregs differentiation and its suppressive function, which may provide a new reference for the treatment of Treg function in many autoimmune diseases, and USP18 can be used as a new therapeutic target for precise medical treatment.